I am assuming that you are looking for x...
7 + √(x - 1) = 2
You must isolate x. To do this you must first subtract 7 to both sides:
7 - 7 + √(x - 1) = 2 - 7
0 + √(x - 1) = -5
√(x - 1) = -5
Now you must get rid of the square root. The opposite order of operation of the square root is squaring. Square both sides of the equation:
(√(x - 1) )² = (-5)²
x - 1 = 25
Now add 1 to both sides to fully isolate x
x - 1 + 1 = 25 + 1
x = 26
Now you must check that this is true:
7 + √(26 - 1) = 2
7 + √(25) = 2
7 + 5 = 2
12 ≠ 2
This is not true which means that this equation has NO solution
Hope this helped!
~Just a girl in love with Shawn Mendes